Pengaruh Terapi Bermain Dengan Media Scrapbook Terhadap Kecemasan Anak Usia Prasekolah Yang Mengalami Hospitalisasi - Marwan Riki Ginanjar (Masker Medika, 2023)
Background : Hospitalization is a condition where a child is hospitalized in a hospital in a planned or emergency condition for treatment until the child’s condition improves when he returns home. The most common anxiety experienced by children is crying, an excessive fear of both officers and new people. One of the interventions that can be done to overcome anxiety in children is by doing Scrapbook therapy. Research Purpose : The purpose of this study was to determine the effect of playing therapy with Scrapbook media on the anxiety of preschool-aged children who were hospitalized at the Palembang Muhammadiyah Hospital. Methods : This study uses a pre-experimental method, with a one group pre test and post test design. The sampling technique used in this study was purposive sampling on pediatric patients treated at the Muhammadiyah Palembang Hospital with a total of 16 respondents. The intervention was given for 30 minutes, carried out once a day during the child’s free time. Result : The result of the nonparametric test using the Wilcoxon Test obtained a p value of < 0.000 (< 0.05). Conclusion : There is an effect of playing therapy with Scrapbook media on the anxiety of preschool-aged children who are hospitalized at the Palembang Muhammadiyah Hospital.